Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/tesq.339
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Cummins (1980), “The Cross‐Lingual Dimensions of Language Proficiency: Implications for Bilingual Education and the Optimal Age Issue.”

Abstract: M y 1980 article argued that cognitive/academic language proficiency (CALP) can be empirically distinguished from basic interpersonal communicative skills (BICS) such as accent, oral fluency, and sociolinguistic competence in both first and second languages (L1 and L2), and that cognitive/academic proficiencies in both L1 and L2 are interdependent, that is, manifestations of a common underlying proficiency. These propositions were then applied to the interpretation of data relating to (a) age and L2 learning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(29 citation statements)
references
References 10 publications
1
25
0
3
Order By: Relevance
“…As a result, the pre-course ELC training adapts the students well to bilingual courses. Linking Cummin's [46] additive bilingualism hypothesis to RQ2, we suggest that the insignificant correlation between CET4/CET6 and Score does not deny the positive role played by English proficiency in a bilingual environment. English proficiency is still an important contributing factor to their success in academic performance as shown in Model (5) in Table 3 of the sensitivity tests.…”
Section: Accounting Majormentioning
confidence: 73%
See 1 more Smart Citation
“…As a result, the pre-course ELC training adapts the students well to bilingual courses. Linking Cummin's [46] additive bilingualism hypothesis to RQ2, we suggest that the insignificant correlation between CET4/CET6 and Score does not deny the positive role played by English proficiency in a bilingual environment. English proficiency is still an important contributing factor to their success in academic performance as shown in Model (5) in Table 3 of the sensitivity tests.…”
Section: Accounting Majormentioning
confidence: 73%
“…Similarly, an empirical study (Han and Yu, [45]) exploring requisite English skills for bilingual education among Chinese university students suggests that students can benefit from bilingual education when they achieve excellent scores in CET4 or CET6. For college students in bilingual education, new reflections by Cummins [46] indicated that older school-age students progress faster than younger students (e.g., students in kindergartens or junior schools) in acquiring L2 academic proficiency, because they can apply their better-developed cognitive/academic language proficiency to L2 learning. Bilingual instruction also brings social benefits, so students are likely to be more motivated when speaking to native speakers and develop more positive attitudes toward L2 (Lasagabaster and Sierra [47], Merisuo-Storm [48]).…”
Section: English Proficiencymentioning
confidence: 99%
“…In later studies he named this idea the linguistic interdependence hypothesis (cf. Cummins, 2016), which ''assumes that two languages are distinct but are supported by shared concepts and knowledge derived from learning, experience, and the cognitive and language abilities of learners'' (Chuang, Joshi, & Dixon, 2012, p. 98). Nearly four decades after first proposing his hypothesis, Cummins concluded that ''The common underlying proficiency makes possible transfer of concepts, skills, and learning strategies across languages'' (Cummins, 2016, p. 940).…”
Section: Cummins' Linguistic Interdependence Hypothesis (Lih)mentioning
confidence: 99%
“…Similarly, an empirical study (Han & Yu, 2007) exploring the requisite English skills for bilingual education among Chinese university students suggested that student can benefit from bilingual education when they achieve excellent level in CET4 or CET6. For college students in bilingual education, new reflections by Cummins (2016) indicate that older school-age students make faster progress than younger students (e.g. students in kindergartens or junior schools) in acquiring L2 academic proficiency because they can apply their better-developed cognitive/academic language proficiency to L2 learning.…”
Section: English Proficiencymentioning
confidence: 99%
“…Cummins (1980) argues that cognitive/academic language proficiency (CALP) is empirically distinguished from basic interpersonal communicative skills (BICS). The distinction between CALP and BICS is nearly universally acknowledged by scholars, educators and policy makers and demonstrated in many research papers and books (Cummins, 2016). However, many researches cannot specifically test CALP and BICS and apply them to the analysis.…”
Section: Contributions Limitation and Future Researchmentioning
confidence: 99%